Fatal Retroperitoneal Hematoma in a Patient Receiving Enoxaparin for Bilateral Pulmonary Emboli - Jordan Sexe; Robin McCarthy; Navid Dara; Lyon Brown; Gaurav Dutta (Case Reports in Hematology)
Venous thromboembolism occurs when a deep vein thrombosis travels to the lungs and forms a pulmonary embolism. Low-molecular-weight heparins are a mainstay in the treatment and prevention of venous thromboembolism and should be initiated promptly due to substantial morbidity and mortality. A rare side effect of low-molecular-weight heparins is major bleeding, which also carries a significant morbidity and mortality rate. Here, we present a case of a fatal retroperitoneal hematoma in a patient being treated with enoxaparin for bilateral pulmonary emboli.